The limits of nationalism - Gans, Chaim (Cambridge University Press, 2003)
This book examines cultural nationalism from a liberal perspective. Chaim Gans examines demands made in the name of cultural nationalism, such as the claim for national self-determination, historical rights to territories and demands for nationality-based priorities in immigration. He argues that only limited forms of these demands are acceptable.
Keywords: Nationalism.; Liberalism.; Free enterprise.; Nationalisme.; Libéralisme.; nationalism.; liberalism.; POLITICAL SCIENCE -- Political Ideologies -- Nationalism.; Free enterprise; Liberalism; Nationalism; Electronic books.